Aldosterone effects on glomerular structure and function. (December 2015) - Bernardi, Stella; Toffoli, Barbara; Zennaro, Cristina; Bossi, Fleur; Losurdo, Pasquale; Michelli, Andrea; Carretta, Renzo; Mulatero, Paolo; Fallo, Francesco; Veglio, Franco; Fabris, Bruno
Objective: Experimental evidence suggests that aldosterone directly contributes to organ damage by promoting cell growth, fibrosis, and inflammation. Based on these premises, this work aimed to assess the glomerular effects of aldosterone, alone and in combination with salt. Methods: After undergoing uninephrectomy, 75 rats were allocated to five groups: control, salt diet, aldosterone, aldosterone + salt diet, aldosterone + salt diet and eplerenone, and they were all studied for four weeks. We focused on glomerular structural, functional, and molecular changes, including slit diaphragm components, local renin–angiotensin system activation, as well as pro-oxidative and profibrotic changes. Results: Aldosterone significantly increased systolic blood pressure, led to glomerular hypertrophy, mesangial expansion, and it significantly increased the glomerular permeability to albumin and the albumin excretion rate, indicating the presence of glomerular damage. These effects were worsened by adding salt to aldosterone, while they were reduced by eplerenone. Aldosterone-induced glomerular damage was associated with glomerular angiotensin-converting enzyme (ACE) 2 downregulation, with ACE/ACE2 ratio increase, ANP decrease, as well as with glomerular pro-oxidative and profibrotic changes. Conclusions: Aldosterone damages not only the structure but also the function of the glomerulus. ACE/ACE2 upregulation, ACE2 and ANP downregulation, and pro-oxidative and profibrotic changes are possible mechanisms accounting for aldosterone-induced glomerular injury.